Hydrogenation of Some Vegetable Oils by Scrap Automobile Catalyst - Fatih Sonmez; Hakan Ercan; Hayriye Genc; Mustafa Arslan; Mustafa Zengin; Mustafa Kucukislamoglu (Journal of Chemistry)
Some vegetable oils were hydrogenated with scrap automobile catalyst (SAC) as a catalyst. The optimum reaction conditions (solvent, reaction time, and catalyst amount) were determined. Our results showed that the linoleic acid was reduced to elaidic acid in the sunflower oil. This procedure not only gives high yields but also allows recycling of automobile wastes as a catalyst in organic reactions and is representative of green chemistry.